Analisis Kebudayaan dan Sistem Pendidikan Islam Kawasan Asia Tenggara (Indonesia, Malaysia, Thailand) - Ali Mursyid Azisi; Lailiyah Qotrunnada (IAIN Sorong, 2021)
Islamic education is not a prison for national education, because Islamic education has a position not only as a compliment but also as the basis for formulating the goals of national education. Islamic education is needed by all Muslims and must be implemented regardless of age or class. Apart from that, it is also aimed at enhancing the human mentality and is also very much needed by many people and countries. Even though there are many characteristics and types of Islamic education in the Southeast Asia region, it has the same goal, namely to improve the quality of humanity and uphold the morals of good, moral, and knowledgeable Muslims. Both national and private education in the countries of Indonesia, Malaysia, and Thailand are very necessary and very important to be studied for Islamic education that is good in behavior, morals and Islamic religious values ​​are well maintained. This article discusses an analysis of the culture and system of Islamic education in the Southeast Asian region, especially Indonesia, Malaysia, and Thailand, which aims to increase understanding of the diversity of Islamic education in Southeast Asia.